Exchange-Rate Adjustment and Macroeconomic Interdependence between Stagnant and Fully Employed Countries - Yoshiyasu Ono (Center for Economic Studies and ifo Institute (CESifo), 2014)
This paper presents a two-country two-commodity dynamic model with free international asset trade in which one country achieves full employment and the other suffers long-run unemployment. Own and spill-over effects of changes in policy, technological and preference parameters that emerge through exchange-rate adjustment are examined. Parameter changes that worsen the stagnant country's current account depreciate the home currency, expand home employment and improve the foreign terms of trade, making both countries better off. The stagnant country's foreign aid to the fully employed country also yields the same beneficial effects.
Keywords: F32; F41; F35; 330; long-run unemployment; fiscal expansion; current account; liquidity trap; exchange rate